Analisis Profitabilitas dan Sales Growth Struktur Modal pada Perusahaan Sektor Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia - Riska Duwi Amalia; Arif Makhsun; M. Muhayin A Sidik (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This study aims to empirically analyze the effect of profitability and sales growth on capital structure in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The background of this research lies in the importance of capital structure decisions in supporting business sustainability and competitiveness, particularly within the highly dynamic food and beverage industry. The sampling method applied was purposive sampling based on specific criteria, resulting in a final sample of 28 companies with a total of 108 observations. Data analysis was conducted using IBM SPSS Statistics version 26 with multiple linear regression as the main analytical technique. The findings reveal that profitability has a negative and significant effect on capital structure, indicating that firms with higher profitability tend to rely less on debt financing. This result aligns with the pecking order theory, which suggests that companies prefer internal financing over external sources. Conversely, sales growth was found to have no significant effect on capital structure, implying that growth in sales is not a decisive factor in financing decisions. These results provide managerial implications, highlighting the role of profitability as a key consideration in determining corporate capital structure policies.